Penile bulb sparing in prostate cancer radiotherapy: Dose analysis of an in-house MRI system to improve contouring - Boeckelmann, F.; Hammon, Matthias; Lettmaier, S.; Fietkau, Rainer; Bert, Christoph; Putz, Florian (Strahlentherapie und Onkologie, 2019)
ObjectiveThis study aimed to assess the reduction in dose to the penile bulb (PB) achieved by MRI-based contouring following drinking and endorectal balloon (ERB) instructions.Patients and methodsA total of 17prostate cancer patients were treated with intensity-modulated radiation therapy (IMRT) and interstitial brachytherapy (IBT). CT and MRI datasets were acquired back-to-back based on a65cm(3) air-filled ERB and drinking instructions. After rigid co-registration of the imaging data, the CT-based planning target volume (PTV) used for treatment planning was retrospectively compared to an MRI-based adaptive PTV and the dose to the PB was determined in each case. The adapted PTV encompassed acaudally cropped CT-based PTV which was defined on the basis of the MRI-based prostate contour plus an additional 5mm safety margin.ResultsIn the seven-field IMRT treatment plans, the MRI-based adapted PTV achieved mean (D-mean) and maximum (D-max) doses to the PB which were significantly lower (by 7.6Gy and 10.9Gy, respectively; p<0.05) than those of the CT-contoured PTV. For 6patients, the estimated PB D-max (seven-field IMRT and IBT) for the adapted PTV was <70Gy, whereas only 1patient fulfilled this criterium with the CT-based PTV.ConclusionMRI-based contouring and seven-field IMRT-based treatment planning achieved dose sparing to the PB. Whereas the comparison of MRI and CT contouring only relates to external beam radiotherapy (EBRT) sparing, considering EBRT and IBT shows the improvement in PB sparing for the total treatment. ZusammenfassungZielZiel war es, eine Dosisreduktion an der Peniswurzel auf Grundlage einer Magnetresonanztomographie-(MRT-)unterstutzten Konturierung unter Einhaltung eines Trink- und Rektalballonprotokolls (ERB) zu erreichen.Patienten und MethodenInsgesamt wurden 17Patienten mit Prostatakrebs intensitatsmoduliert bestrahlt (IMRT) und erhielten anschlie ss end eine interstitielle Brachytherapie (IBT). Computertomographie- (CT) und MRT-Datensatze wurden kurz nacheinander auf Basis eines 65-cm(3)-ERB- und Trinkprotokolls akquiriert und danach rigide registriert. In beiden Datensatzen wurde jeweils die Peniswurzeldosis bestimmt. Ein CT-basiertes Planungszielvolumen (PTV) wurde fur die Bestrahlungsplanung verwendet und retrospektiv mit einem MRT-basierten adaptiven PTV verglichen. Das adaptive PTV umfasst ein kaudal gekurztes CT-basiertes PTV, welches auf Grundlage einer MRT-basierten Prostatakontur und einem zusatzlichen 5-mm-Sicherheitsraum definiert wurde.ErgebnisseDas MRT-basierte adaptive PTV erzielte bei der 7-Felder-IMRT-Planung 7,6Gy (D-mean) und 10,9Gy (D-max) weniger Dosis an der Peniswurzel als das CT-konturierte PTV. Fur 6Patienten, geplant mit dem adaptiven PTV, war die abgeschatzte Maximaldosis D-max (7-Felder-IMRT+IBT) an der Peniswurzel <70Gy, wohingegen beim CT-basierten PTV nur 1Patient das Kriterium erfullte.SchlussfolgerungDie MRT-basierte Konturierung und die 7-Felder-IMRT-Planung reduzierte die Peniswurzeldosis. Die Gesamtdosis der Peniswurzel bestehend aus der 7-Felder-IMRT- und IBT-Planung zeigte sich reduziert, wobei die MRT- und CT- Konturierungsanalyse nur auf die externe 7-Felder-Bestrahlungsplanung basiert.
CRIS-Team WoS Importer:2019-02-21